Effect of CaTiO3 Crystal Structure and Cathodic Morphological Structure on the Electrolysis - Ru, Liyue; Li, Zequan; Bai, Chenguang; Zhang, Na; Wang, Haihua (Asian Journal of Chemistry, 2012)
TiO2 and CaTiO3 were electrolyzed in molten CaCl2 to investigate the different electrochemical behaviours of in situ and ex-situ CaTiO3 and the caused reason of the difference. The products were detected by X-ray diffraction, scanning electron microscope and BET specific surface area analyzer. It was shown that, electrolysis of ex-situ CaTiO3 as starting material exhibited remarkable advantages for the crystal structure and morphological structure. Ex-situ CaTiO3 has been deviated before the process, but the crystal distortion of in situ CaTiO3 formed via TiO2 is later than ex-situ CaTiO3, lattice distortion is helpful for the removal of Ca2+ and O2-, which is good for the electrolysis of ex-situ CaTiO3; the specific surface area of ex-situ CaTiO3 is larger than in situ CaTiO3 formed via TiO2, which may promote the formation of more reactive sites; the porosity of ex-situ CaTiO3 is larger than in situ CaTiO3 formed via TiO2, owning more and larger pore is favorable of ion migration.